Mechanical and Thermal Properties of Kenaf Fiber Reinforced Polypropylene/Magnesium Hydroxide Composites. Issue 2 (June 2017) - Lee, C. H.; Sapuan, S. M.; Hassan, M. R.
This paper presents a study of the mechanical and thermal properties of kenaf fiber (KF) reinforced polypropylene (PP)/magnesium hydroxide (MH) composites. Pure PP samples show low tensile, flexural and flame retardant properties. It was found that KF and MH filler insertion improved the properties of PP composites. The incremental addition of KF fiber between 0 and 20 weight percent in composites results in higher tensile modulus and decomposed mass loss at onset temperature, but lower tensile strength, elongation, flexural strength and onset temperature. Addition of 25 wt% KF produces slightly higher flexural strength. Increasing the volume of MH filler in the composites caused lower strength, tensile modulus and elongation, but higher onset temperature and 2 nd peak temperature in thermogravimetric analysis (TGA) testing. Increasing the KF content in the PP matrix resulted in lower mass residue. Increasing the KF content in composites containing MH increased the mass residue at the end of the testing.